Filsafat Kapabilitas dan Kemungkinan Politik Pengakuan yang Mutual (Merekonstruksi Filsafat Praktis Paul Ricoeur) - Felix Baghi (Institut Filsafat dan Teknologi Kreatif Ledalero, 2021)
This article focuses on Capability Approach in Philosophy and the Possibility of Politics of Recognition: to reconstruct Ricoeur’s practical philosophy. Based on his philosophical question: what is capable self? we search for the meaning of human capability which will imply an understanding of the self and the recognition of its basic personal capacities, from where proceeds mutual recognition. Since this is the main goal of Ricoeur, I choose to expose this part of his work with the objective of structuring its ethical aim, which is to live good life with and for others in just institutions. Here, love, justice and the poetics of the gift will play significant roles. This study is divided into three main parts. Part One is a discussion of the phenomenology of the capable self that aims to emphasize the meaning of personal capacities in terms of self’s ability. Part Two presents ethics and the politics of recognition in three sub-themes: self-esteem, solicitude for others and justice in institutions. This leads to the Part Three which completes the previous study by analyzing the relationship between love, justice and possibility of the politics of mutual recognition.Keywords: Capable self, Mutual Recognition, Ethical Aim and the Poetics of the Gift.